The Effectiveness of Using Polishing Technology in Creating Premium Quality Rice (Case Study of UD. Barokah Parepare) - Ahmad Dzacky Maarief; Abd Rahim; Nurhapsa (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Rice is a strategic food commodity whose quality is increasingly becoming a concern for consumers, especially in the premium segment. Polishing technology is one of the important innovations in improving the visual and physical quality of rice. This study aims to analyze the effectiveness of the use of polishing technology in creating quality premium rice in UD. A new pair of shoes. This study uses a qualitative descriptive approach with data collection techniques in the form of in-depth interviews, field observations, and documentation, and is supported by consumer questionnaires as complementary data. Informants consist of owners, machine operators, and workers who understand the production process firsthand. The data were analyzed through the Miles and Huberman model with three stages: reduction, presentation, and conclusion drawn. The results showed that the effectiveness of polishing was greatly influenced by the quality of raw materials, moisture management, and tool maintenance. Product quality evaluation is carried out visually based on experience, with a maximum tolerance limit of 15% for broken rice. Consumers give positive ratings of physical, taste, and packaging attributes, and show a willingness to pay more for consistent premium quality. This research emphasizes the importance of integration between technical control of production and understanding of consumer preferences in maintaining the quality of premium rice in the local market.